PRESERVATION OF VISUAL CULTURAL HERITAGE THROUGH THE MANAGEMENT OF DIGITAL ILLUSTRATIONS OF NUSANTARA MANUSCRIPTS AT THE NATIONAL LIBRARY OF THE REPUBLIC OF INDONESIA - Belian Sunja Sari; Fransiska Timoria Samosir; Diyas Widiyarti (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
The digitization of Indonesian manuscripts is not only related to the preservation of texts, but also includes visual information such as illustrations and illuminations. Previous studies have focused more on the technical aspects of digitization, while the representation of illustrations in metadata is still rarely studied. In fact, without a clear representation, illustrations are difficult to trace and utilize as cultural information. This study aims to examine the management of illustrations of Indonesian manuscripts in digital form and analyze their representation in metadata on the Khastara portal at the National Library of the Republic of Indonesia. The method used is a qualitative case study approach through non-participatory observation techniques, interviews, and literature review with five informants. Data analysis refers to the Digital Cultural Heritage Standards framework: From Silo to Semantic Web, which includes elements of METS, Semantic Web, and Enricher. The research findings show that digitization is carried out systematically and is able to record illustrations well visually. However, in metadata, illustrations are still presented as part of the general description of the manuscript and have not been positioned as independently accessible information. This condition indicates that the function of metadata is still limited to collection description and does not fully support the traceability of visual information. This research confirms that metadata development needs to be directed at the ability to represent illustrations as structured visual information. This is crucial so that digital repositories function not only as storage but also as a means of broader access and utilization of cultural heritage.